A collection of SWOT factors (strength, weaknesses, opportunities and threats) for hybrid energy networks. (October 2021) - Schmidt, Ralf-Roman; Leitner, Benedikt
Abstract: District heating and cooling (DHC) systems traditionally have strong links to electricity and gas networks via combined heat and power (CHP) processes. However, the role of CHP plants will significantly change due to a growing competition for renewable fuels and an increasing share of renewable electricity production. Consequently, other heat sources will be needed for DHC networks in the future. Here, especially heat pumps will play a major role, but also power-to-gas processes can contribute via recovering its waste heat, thus creating different coupling points between the DHC, electricity and gas system. By an optimized planning and operation of locally available coupling points a "hybrid energy network" (HEN) can be created. To analyze the strengths, weaknesses, opportunities, and threats (SWOT analysis) of hybrid energy systems, a three-stage process is being conducted based on a literature search, qualitative input from experts during a dedicated workshop and a comprehensive feedback and discussion phase with experts. Currently, the first two stages of the method have been completed, collecting a wide range of inputs, comments and feedback from the different experts of the IEA ISGAN Annex 6 "Power Transmission and Distribution Systems" and the IEA DHC Annex TS3 "Hybrid Energy Networks". Results: besides a novel classification approach for Hybrid Energy Networks, different SWOT factors were collected, e.g. strengths include the potential to cost-efficiently support the integration of Wind and PV electricity as well as to decarbonize heating and cooling demands. Weaknesses include their complexity, the required investments into coupling points and (current) regulatory restrictions. Opportunities include by trend increasing incentives for flexibility and efficiency services, upcoming (green) financing options and regulations. Threats include possible disruptions of existing business models and uncertainties of the future development including the regulatory framework as well as competing flexibility services.